Examining corporate support issues with health literacy as a key factor: The Case of a Hiroshima corporation - Yuan Li; Hiromi Kawasaki; Satoko Yamasaki; Sae Nakaoka; Misa Shiraishi; Zhengai Cui (Journal of Family Medicine and Primary Care)
Context: Given the dramatic decline in Japan's labor force, promoting women's participation in the workforce is essential. Aims: We aimed to take a Hiroshima company as an example and analyze the influencing factors of health literacy (HL) to clarify the issues of the active participation of female employees. Methods and Materials: From February to March 2023, a cross-sectional study was conducted by a company in Hiroshima prefecture that contained many male employees. A total of 1,114 valid respondents were received. Employees' demographics, menstrual-related concerns, women's activity promotion support, and HL were investigated in this study. Statistical Analysis Used: The Chi-square test and logistic regression using SPSS statistical software version 25 were used. Results: There were significant differences between high and low HL with age, women's menstrual problems, and women's activity promotion support. The participants who were unaware of women's menstrual-related problems and their company's implementation of women's activity promotion support were more likely to have high HL. In addition, female employees (including female management) and male management have significantly different cognitions about women's activity promotion support. Conclusions: This study found that overall HL among employees in male-dominated companies is low, even among participants who were aware of women's menstruation-related health issues and the company's women's activity promotion support. Increased women's representation in management can bridge policy perception gaps. Male-dominated companies should enhance HL via career programs, health education, and improved communication for active female engagement.